EKSPLORASI DAMPAK PROGRAM INFAQ DAN SHODAQAH TERHADAP PENGEMBANGAN KARAKTER PEDULI SOSIAL DI SEKOLAH DASAR ISLAM DI MEDAN - Suherman; Basri, Muhammad (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
This research explores the long-term impact of Infaq and Shodaqah programmes on the moral and social development of students in Medan city. Using a Qualitative approach, this research integrates qualitative surveys to provide a comprehensive understanding of the impact of these programmes. The analysis showed that students who participated in the Infaq and Shodaqah programmes demonstrated significantly stronger moral reasoning and social behaviours, such as empathy and cooperation, compared to their non-participating counterparts. Qualitative findings further supported these results, emphasising the role of these programmes in reinforcing Islamic values and fostering a strong sense of community among students. This study concludes that Infaq and Shodaqah programmes are effective tools for character education, contributing to the development of socially responsible and highly moral individuals. The findings highlight the importance of integrating such programmes into the broader educational framework to enhance students' overall ethical and social development.